IMPLEMENTATION OF ELEMENTARY SCHOOL CHILDREN'S MORAL EDUCATION - Enny Rahayu; Aisha Aisha; Melyani Sari Sitepu (Proceeding International Seminar of Islamic Studies, 2023)
Moral education exists at every level of education. In elementary school, moral education has never been separated from the noble values that exist in the Indonesian nation's moral order which are clearly exposed in Pancasila. Moral education has a very noble aim, namely to form children as individuals who are religious, have a sense of humanity, uphold the values of deliberation for democracy and justice. Moral education in schools needs to be carried out seriously to build a quality generation of the nation. Although the role of educating school children's morals is their parents, teachers at school also play a major role in realizing the morals that children should have. Education as an effort to change children's behavior to be better, especially in educating morals from early childhood to elementary school age children. The purpose of writing this article is to describe the application of moral values education at SDN 106217 Lr.Amaliun Tanjung Beringin. The method used is a qualitative research method. So that the result is good moral values, noble character, courtesy.